ANALISA KARAKTERISTIK PEKERJAAN, DISIPLIN KERJA, DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN - Yuni Putri Maulani (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The aim of this research is to analyze the influence of job characteristic, work discipline, and career development on employee performance at PT. Antarakata Group Semarang. The data type which been used in this research is primary data that already obtained from the real source questionere. This research sample is taken from PT. Antarakata Group employees amount 52 persons. The sampling technique is using random sampling. This research examination tools are : validity examination using KMO-MSA factor analysis, the reliability examination using Cronbach Alpha and hypothesis examination using multiple linear regression. The reasearch’s results are : 1. The job characteristic has significant and positive influence, 2. Work discipline doesn’t have significant influence, 3. Career development has significant and positive influence.